2022
DOI: 10.31234/osf.io/4qmzk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Prediction Error on Episodic Memory Encoding is Modulated by the Outcome of the Predictions

Abstract: Predictive processing accounts propose that our brain constantly tries to match top-down internal representations with bottom-up incoming information from the environment. Predictions can lead to prediction errors of varying degrees depending on the extent to which the information encountered in the environment conforms with prior expectations. Theoretical and computational models assume that prediction errors have beneficial effects on learning and memory. However, while there is strong evidence on the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Studies taking this approach generally found a positive relation between PE and memory (Calderon et al, 2021;Davidow et al, 2016;De Loof et al, 2018;Jang et al, 2019;Pupillo et al, 2023;Rosenbaum et al, 2022;Niv, 2019, 2021;Rouhani et al, 2018). This PE-driven enhancement of recognition memory does not depend on specific characteristics of the task, such as whether the values of the stimuli were learned before or during the encoding task, whether the outcome was monetary or not, and whether the recognition test was intentional or incidental.…”
Section: What We Know: the Effect Of Pe On Memorymentioning
confidence: 95%
See 4 more Smart Citations
“…Studies taking this approach generally found a positive relation between PE and memory (Calderon et al, 2021;Davidow et al, 2016;De Loof et al, 2018;Jang et al, 2019;Pupillo et al, 2023;Rosenbaum et al, 2022;Niv, 2019, 2021;Rouhani et al, 2018). This PE-driven enhancement of recognition memory does not depend on specific characteristics of the task, such as whether the values of the stimuli were learned before or during the encoding task, whether the outcome was monetary or not, and whether the recognition test was intentional or incidental.…”
Section: What We Know: the Effect Of Pe On Memorymentioning
confidence: 95%
“…However, regarding PE effects at outcome, the findings diverge (Ergo et al, 2020). In fact, while some studies have found unsigned PEs effects at outcome (Rouhani and Niv, 2021;Rouhani et al, 2018), others have reported outcome-related signed PEs effects (Calderon et al, 2021;De Loof et al, 2018;Pupillo et al, 2023).…”
Section: (Caption On Next Page)mentioning
confidence: 99%
See 3 more Smart Citations